Hidrofilne ogrodne tablete s prirejenim sproščanjem na osnovi izbranih naravnih polimerov - Pavli, Matej (Farmacevtski vestnik, 2016)
Matrix tablets are one of the most commonly used controlled release dosage forms, in which the matrix is formed from one or a combination of different biocompatible polymers. Many release mechanisms of the drug from such system can be obtained, de- pending on a polymer type and physico-chemical characteristics of a drug. Natural polymers offer new technological possibilities and represent prom- ising alternatives to commonly used, well re- searched synthetic and semisynthetic polymers. Hence, intensive research of natural polymers has been conducted recently. However, matrix tablets based on natural polymers present a challenge due to lack of knowledge of their behaviour on molecular scale, hence their susceptibility to different factors, which can affect the drug release are hard to predict. The repeatability of natural polymers charac- teristics between different batches can also be un- d er question, which again might influence the prop- erties of the final dosage form. In this review article we will summarize our investigations of three prom- ising natural polymers and overview the studies fo- cused on their use in hydrophilic matrix tablets for controlled release.
Keywords: farmacevtski pripravki; karagenani; ksantan; nadzorovano sproščanje; naravni polimeri; semenska sluz rožičevca; tablete